Performance of a turbo-coded downlink IDMA system using transmitter pre-processing. (July 2016) - Rajmohan, R.; Vishvaksenan, K.S.; Mira, M.; Subramanian, Sudharssun
Highlights: We investigate the BER performance of turbo coded IDMA system using transmitter pre-processing for DL transmission. Performance is analyzed using ZF-MUTP when communicating over SUI and LTE channel models specifications. BER Performance is compared for ZF-MUTP assisted IDMA system considering both an equal power approach and a maximum-signal-to-noise ratio (MSNR) approach. Coded IDMA system with MUTP based on MSNR power allocation regime results in a superior BER performance with less SNR when compared to the equal power allocation policy. Abstract: In this study, we investigate the bit error rate (BER) performance of a multi-user transmitter pre-processing (MUTP) aided, turbo-coded interleave division multiple access (IDMA) scheme over correlated frequency-selective channels for downlink (DL) communication. We realize MUTP using a zero forcing (ZF) approach. Further, we build the pre-processing matrix using the channel state information of all of the active users. To be specific, we evaluate the BER performance of a coded ZF-MUTP assisted IDMA system for a realistic channel model based on Stanford University Interim channel and Long term Evolution channel specifications; the MUTP is based on both an equal power approach and a maximum-signal-to-noise ratio (MSNR) approach. From our simulation results, we observe that our considered system with a MSNR power allocation regime provides better performance in terms of the achievable BER than the equal power approach, while offering a low complexity receiver for DL transmission. Graphical abstract: